2018
DOI: 10.1016/j.scitotenv.2017.12.086
|View full text |Cite
|
Sign up to set email alerts
|

Wildland fire smoke and human health

Abstract: The natural cycle of landscape fire maintains the ecological health of the land, yet adverse health effects associated with exposure to emissions from wildfire produce public health and clinical challenges. Systematic reviews conclude that a positive association exists between exposure to wildfire smoke or wildfire particulate matter (PM) and all-cause mortality and respiratory morbidity. Respiratory morbidity includes asthma, chronic obstructive pulmonary disease (COPD), bronchitis and pneumonia. The epidemio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
380
1
14

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 438 publications
(401 citation statements)
references
References 44 publications
6
380
1
14
Order By: Relevance
“…C. Liu et al, 2017; Wegesser et al, 2010; Wong et al, 2011), because wildfire PM 2.5 predominantly comes from burning trees and underbrush, resulting in higher organic aerosols than those in urban air pollutions (Alves et al, 2011; Na & Cocker, 2008). Moreover, urban PM 2.5 tends to generate chronic, low-level exposures, whereas wildfire smoke is often related to acute, high concentration exposures (Cascio, 2018). Therefore, epidemiologic studies assessing the specific health impacts of wildfire PM 2.5 are important to better understand its public health and environmental risks.…”
Section: Introductionmentioning
confidence: 99%
“…C. Liu et al, 2017; Wegesser et al, 2010; Wong et al, 2011), because wildfire PM 2.5 predominantly comes from burning trees and underbrush, resulting in higher organic aerosols than those in urban air pollutions (Alves et al, 2011; Na & Cocker, 2008). Moreover, urban PM 2.5 tends to generate chronic, low-level exposures, whereas wildfire smoke is often related to acute, high concentration exposures (Cascio, 2018). Therefore, epidemiologic studies assessing the specific health impacts of wildfire PM 2.5 are important to better understand its public health and environmental risks.…”
Section: Introductionmentioning
confidence: 99%
“…Fire smoke is a mixture of hundreds of different aerosols and gases. In the context of open burning, PM can be considered as a marker of this mixture and it is recognized as the primary driver of adverse health impacts from fire smoke [1,8].…”
Section: Discussionmentioning
confidence: 99%
“…The previous studies in the setting of landscape fire smoke exposure have shown an increase in acute respiratory conditions [4,5], cardiac arrest [6], cardiovascular mortality [1], non-traumatic emergency department attendances [7] and all-cause mortality [1,8,9], with the elderly and people with pre-existing health conditions being most at risk [5].…”
Section: Introductionmentioning
confidence: 98%
“…Even healthy individuals experience respiratory, ear-nose-throat symptoms, difficulty sleeping, viral infections, and other subclinical or precursor events that reduce productivity and can result in delayed but serious health outcomes (Integrated Science Assessment (ISA) for Particulate Matter, 2009;Krewski et al, 2005). Reducing the amount, duration, and intensity of smoke exposure by using an air filter and limiting outdoor activities is widely recommended as a health preventive action (Cascio, 2018;Wildfire Smoke: A Guide for Public Health Officials, 2016). To achieve better public health outcomes, we need to apply what we know about health risks and protective health behavior effectively.…”
Section: Introductionmentioning
confidence: 99%